Cerebrospinal Fluid Protein Level and Nerve Conduction Study as Short-Term Prognostic Marker of Guillain Barré Syndrome - Kamal, Mohammad Mostafa; Habib, Mansur; Islam, Md Rafiqul; Ghose, Swapan Kumar; Uddin, Kazi Gias; Chowdhury, Ahmed Hossain; Shaha, Konol; Amin, Robed; Sina, Hashmi; Dhar, Kinghshuk (Bangladesh Journal of Neuroscience, 2018)
Background: Guillain Barré Syndrome (GBS) diagnosis is based on a combination of clinical features, Nerve conduction studies (NCS) and analysis of the cerebrospinal fluid (CSF) which eventually assist in monitoring disease progression as well as the efficacy of immunotherapy. The main objective of this study was to determine the relation of CSF protein level and nerve conduction study with short-term prognosis of GBS patients. Methods: This observational study was carried out in the Department of Neurology and Medicine, Dhaka Medical College Hospital, Dhaka during the period August, 2017 to July, 2018. Total 50 patients suffering from GBS were enrolled in this study. Lumber puncture (LP) and NCS were done at day 10 of symptom onset. Results: In this study majority (87.5%) of the patients had GBS Disability score <3 in demyelinating and 16(47.1%) in axonal on day 90. Three fourth (75.0%) patients EGRIS score was ³3 in demyelinating and 34(100.0%) in axonal and mEGOS it was revealed that more than two third (68.8%) patients mEGOS score was ³6 in Demyelinating and 33(97.1%) in axonal. More than three fourth (76.0%) patients ³6 mEGOS score in CSF protein <100 (mg/dl) and 25(100.0%) in CSF protein ³100 (mg/dl). Multiple logistic regression analysis showing a subject with axonal GBS had 1.579 (95.0% C.I 1.717 to 3.475), CSF Protein had 1.013 (95.0% C.I. 1.001 to 1.026) (PÂ0.05%). Conclusion: CSF analysis for protein and NCS examination appeared as the essential short term predictors in evaluating diagnostic accuracy and prognostic determinant of GBS early. Bangladesh Journal of Neuroscience 2018; Vol. 34 (2): 79-84